Grecka koncepcja pankalii a wczesnochrześcijańskie ujęcie piękna świata - Kijewska, Agnieszka (Vox Patrum, 1986)
This paper refers to the fundamental problem of aesthetics in the period of later Greek and early Medieval thought.